THE SPECIES COMPOSITION, DISTRIBUTION, BIOMASS OF MOLLUSK (CLASS: GASTROPODA, BIVALVIA, CEPHALOPODA) IN CORAL REEF IN 19 SURVEYED ISLANDS IN VIETNAM - An, Do Thanh; Khuong, Do Van; Duy, Do Anh (Vietnam Journal of Marine Science and Technology, 2014)
In 2010-2011, the project “Comprehensive surveys on biodiversity in coral reef ecosystems and islands in Vietnam sea aiming at the sustainable development” carried out the assessment of the species composition, distribution, biomass of mollusk in coral reef at 19 islands in Vietnam sea. By applying the morphological method, the results of status and resource of mollusk showed that 227 species belonged to 44 families, 13 orders of 3 classed of mollusk. Among them, there were 163 species of Gastropoda, 57 species of Bivalvia and 7 species of Cephalopoda. In terms of geographical distribution: The highest distribution was in Phu Quy island with 146 species, followed by Cat Ba - 144 species, Tho Chu -144 species, Cu Lao Cham - 137 species, Hai Van - Son Cha - 137 species, Nam Yet - 135 species, etc. Tran island had the lowest distribution with 81 species only. The depth distribution: Shallow water areas had 137 species, deep water areas had 115 species, there were a lot of species distributing in both. The similarity index of mollusk species composition between studied islands was average, around 0.35 - 0.68. Biodiversity index was around 0.53 - 1.52. Individual density was around 37 - 105 individuals/m2, the average was about 54 individuals/m2. Average biomass was about 5,029.2 gr/m2. There were 41 often exploited species for food, handicrafts, medicine. Among them, there were 4 vulnerable species (VU), 3 endangered species (EN) and 2 critically endangered species (CR).